Coping With Staff Burnout and Work-Related Posttraumatic Stress in Intensive Care*. Issue 7 (July 2017) - Colville, Gillian A.; Smith, Jared G.; Brierley, Joe; Citron, Kim; Nguru, Noreen M.; Shaunak, Priyanka D.; Tam, Olivia; Perkins-Porras, Linda
Abstract : Objectives: To examine the associations with symptoms of 1) burnout and 2) work-related posttraumatic stress, in adult and pediatric intensive care staff, focusing on the particular contributions of resilience and coping strategies. Design: Point prevalence cross-sectional study. Setting: Three adult ICUs and four PICUs. Subjects: Three hundred seventy-seven ICU staff. Interventions: None. Measurements and Main Results: Brief Resilience Scale, abbreviated Maslach Burnout Inventory, Trauma Screening Questionnaire, and Hospital Anxiety and Depression Scale. Prevalence of burnout (defined as high emotional exhaustion or high depersonalization) was 37%. Prevalence of clinically significant posttraumatic stress symptoms was 13%. There was a degree of overlap between burnout and other measures of distress, most notably for anxiety (odds ratio, 10.56; 95% CI, 4.12–27.02; p < 0.001). Hierarchical logistic regression demonstrated that self-reported resilience was strongly associated with decreased likelihood of meeting criteria for both forms of work-related distress (burnout: odds ratio, 0.52; 95% CI, 0.36–0.74; p < 0.001 and posttraumatic stress: odds ratio, 0.28; 95% CI, 0.16–0.46; p < 0.001) and that physicians were twice as likely as nurses to be at risk of reporting burnout (odds ratio, 2.11; 95% CI, 1.18–3.78; p = 0.012). After controlling for resilience, profession, and setting, the following coping strategies were independently associated with outcomes: attending debriefing reduced risk of burnout (odds ratio, 0.45; 95% CI, 0.21–0.95; p = 0.036), whereas the odds of posttraumatic stress were less if staff used talking to seniors (odds ratio, 0.43; 95% CI, 0.20–0.92; p = 0.029) or hobbies (odds ratio, 0.46; 95% CI, 0.23–0.93; p = 0.030) to cope with stress at work. Venting emotion (odds ratio, 1.92; 95% CI, 1.12–3.31; p = 0.018) and using alcohol (odds ratio, 2.30; 95% CI, 1.26–4.20; p = 0.006) were associated with a doubling in risk of reporting burnout. Conclusions: The use of particular coping strategies was systematically associated with symptoms of burnout and work-related posttraumatic stress in this group of intensive care staff, even after controlling for resilience and other factors. More research on how best to promote adaptive coping is needed in these challenging settings. Abstract : Supplemental Digital Content is available in the text.